2017
DOI: 10.1021/acs.est.7b00635
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Bag Derived-Microplastics as a Vector for Metal Exposure in Terrestrial Invertebrates

Abstract: Microplastics are widespread contaminants in terrestrial environments but comparatively little is known about interactions between microplastics and common terrestrial contaminants such as zinc (Zn). In adsorption experiments fragmented HDPE bags c. one mm in size showed similar sorption characteristics to soil. However, when present in combination with soil, concentrations of adsorbed Zn on a per mass basis were over an order of magnitude lower on microplastics. Desorption of the Zn was minimal from both micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(170 citation statements)
references
References 67 publications
4
157
0
Order By: Relevance
“…For instance, hydrophobins are amphiphilic proteins ubiquitous in soils that are secreted by fungi (Rillig, 2005 (Steinmetz et al, 2016), ingestion by terrestrial and continental birds (Gil-Delgado et al, 2017;Holland et al, 2016;Zhao et al, 2016), reduction in growth of earthworms (Lwanga et al, 2016), lethal toxicity to fungi (Miyazaki et al, 2014(Miyazaki et al, , 2015Nomura et al, 2016), mammal lung inflammation (Hamoir et al, 2003;Oberdorster, 2000;Schmid & Stoeger, 2016) and broad cytotoxicity (Forte et al, 2016;Kato et al, 2003) of nanoplastics [Colour figure can be viewed at wileyonlinelibrary.com] stability, with direct potential consequences for soil erosion and biogeochemical cycles (Rillig, 2005). It was suggested that microplastics might present distinct sorption properties for soil inorganic elements (Hodson, Duffus-Hodson, Clark, Prendergast-Miller, & Thorpe, 2017), and laboratory results suggest that hydrophobins play a role in the protection against nanoplastic toxicity to filamentous fungi (Nomura et al, 2016). Relevant biogeochemical changes might arise if the hydrophobic surfaces of microplastics interact with hydrophobins or other chemical drivers of soil structure in a manner significantly different from natural soil particles.…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hydrophobins are amphiphilic proteins ubiquitous in soils that are secreted by fungi (Rillig, 2005 (Steinmetz et al, 2016), ingestion by terrestrial and continental birds (Gil-Delgado et al, 2017;Holland et al, 2016;Zhao et al, 2016), reduction in growth of earthworms (Lwanga et al, 2016), lethal toxicity to fungi (Miyazaki et al, 2014(Miyazaki et al, , 2015Nomura et al, 2016), mammal lung inflammation (Hamoir et al, 2003;Oberdorster, 2000;Schmid & Stoeger, 2016) and broad cytotoxicity (Forte et al, 2016;Kato et al, 2003) of nanoplastics [Colour figure can be viewed at wileyonlinelibrary.com] stability, with direct potential consequences for soil erosion and biogeochemical cycles (Rillig, 2005). It was suggested that microplastics might present distinct sorption properties for soil inorganic elements (Hodson, Duffus-Hodson, Clark, Prendergast-Miller, & Thorpe, 2017), and laboratory results suggest that hydrophobins play a role in the protection against nanoplastic toxicity to filamentous fungi (Nomura et al, 2016). Relevant biogeochemical changes might arise if the hydrophobic surfaces of microplastics interact with hydrophobins or other chemical drivers of soil structure in a manner significantly different from natural soil particles.…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
“…Such effects might be partially explained by histological damage and changes in the gene expression associated with microplastic exposure (Rodriguez-Seijo et al, 2017). Moreover, microplastics could act as vector of toxic Zn to earthworms under environmental conditions due to a higher adsorption of this metal to high density polyethylene microplastic (Hodson et al, 2017). Lethal effects (100% mortality) were observed after 1 h exposure of yeast cells of Saccharomyces cerevisiae to polystyrene nanobeads (50 and 100 nm, 10-15 mg/L) in 5 mM NaCl culture media (Miyazaki et al, 2014).…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
“…From an ecotoxicological point of view, MPs have been detected in different aquatic organisms since they can be ingested, and accumulation along the food web has been observed in different settings [86,90,144]. Moreover, plastic particles can act as vectors of toxic chemicals to the biota [106,178]. Nonetheless, the toxic effects of MPs, especially regarding adsorption-desorption equilibria in environmental conditions, need to be investigated further, since the vector effect of MPs for pollutants still presents contradictory results [124,125].…”
Section: Future Perspectives In Microplastic Research For Freshwatersmentioning
confidence: 99%
“…Though polymers were considered to be inert towards metals in the past [97], great attention has recently been paid to better understanding the interaction between heavy metals and microplastics [98][99][100][101][102][103][104][105][106][107][108].…”
Section: Heavy Metalsmentioning
confidence: 99%